Jual Beli Online Yang Mencantumkan Gambar Dan Testimoni Palsu Studi Market Pleace Melalui Media Facebook - Lilik Erliani (Falah: Jurnal Hukum Ekonomi Syariah, 2020)
Businesses in the field of buying and selling are advancing, technological advances are becoming one of the media for meeting traders and buyers by offering their merchandise through social networks ranging from official online buying and selling forums or personal applications such as Facebook line, and Instagram. In this study, the writer will focus on faceook media because even though we know that there are official and safe applications for online buying and selling media, it still does not rule out a lot of traders and buyers selling their wares and shopping for goods using other online media such as Facebook is one of them. Only by using a clear camera and testimonials from previous buyers, potential buyers will be interested in items sold at market pleace via Facebook. Even though we know that a good picture may not necessarily show the original quality of goods as good as in the picture because the image on a smart phone is the result of a good camera quality, and about the testimonials or comments of consumers who have shopped at these stalls, it is not necessarily true. The shopper could have made a fake account and then made testimonials on his merchandise so as to attract the sympathy of potential buyers to buy these merchandise. Based on this, the author wants to examine how the law of buying and selling online by using testimonials and false images in the perspective of Islamic law ?. This study uses a qualitative approach to the type of library research. To obtain the data needed, this study uses data collection techniques in the form of documentation, then analyzed with a descriptive qualitative method by describing the problem and comparing it with the analysis that is used, From the research conducted, the results of the research based on the first problem formulation, namely buying and selling that includes fake images from the perspective of the cleric, are invalid because the nature of the object is not clearly known and there is an element of rara, but if the buyer does not feel disadvantaged by the existence of a false image, buying and selling is allowed and is considered as a special dispensation and dispensation for business people. The results of research based on the formulation of the second problem namely buying and selling false testimonials is prohibited because it is prohibited because sha> ra '(not in accordance with Islamic provisions and is still disputed by scholars) because it includes in the buying and selling najasy and the existence of elements of fraud